Reasoning Socratic Questioning Method to Enhance University Students' Critical Reading in Critical Reading Course - Ummi Abidah, Unsia Fika (RETAIN : Journal of Research in English Language Teaching, 2022)
In this super busy era, students have to know how to ‘digest’ bunch of knowledge or information around them. Every place, even every hour they will have a big chance to find it. In order to build student’s perspective broader, first thing to know is about the tools that can help them to survive. This study was aimed to explore ‘what and how’ to learn reading skill in a proper way. In short, people who want to establish their learning skill of reading through it, they could take the advantage of the method for them selves not only in academic purposes but also in daily life too. This method is well-known as socratic questioning method. For the participants, the researcher has taken 5 university students from English department to filled 10 questions in the questionnaire and also to be interviewed. This study used descriptive qualitative as a research design. The researcher gave an example from a pattern of socratic method and 4 out of 5 agree that the method has asked university students to think critically, and further than that, its method also help them to read critically when they thought it is essential to read with the critical analysis. The way how they to process critical reading are quite similar but different, understanding the main ideas, finding literature review, then, breaking it down. To reach the socratic method, the students have to pass these 5 stages; wonder, hypothesis, elenchus, acceptance/rejection, action. Socratic method did not only answer their question, but also help them to analyze as further information as they keep looking for it. It is also showed that university students have to read more about some methods that can help them to read critically because there are still lots of students who do not know what socratic questioning method is.